PENGEMBANGAN MEDIA FLASHCARD INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN KAMALAKA - Suhernah; Anna Maria Oktaviani; Ari Gunardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the limited variety of learning media used in beginning reading instruction for first-grade students at SDN Kamalaka. Preliminary observation and a teacher interview indicated that a number of students still had difficulty recognizing letters, blending letters into syllables, and reading simple words, while the media available in the classroom were still confined to textbooks and the whiteboard. This study aimed to describe the process of developing Interactive Flashcard media and to determine its feasibility for beginning reading instruction. The study used a Research and Development (R&D) method with the 4D model, consisting of Define, Design, Develop, and Disseminate. Data were collected through preliminary observation, a teacher interview, documentation, and validation sheets completed by media, content, and language experts, and were analyzed using a feasibility-percentage formula and descriptive analysis. The results showed that the media expert validation reached 85.94%, the content expert validation 83.75%, and the language expert validation 91.00%, with an average product feasibility of 86.90%, categorized as highly feasible. The supporting instruments were also validated, reaching 84.00% for the non-test instrument and 85.33% for the test instrument. Limited implementation of the media, guided by a lesson plan, showed that the product could be applied systematically in the classroom. Therefore, the Interactive Flashcard media developed through the 4D model is highly feasible as supporting media for beginning reading instruction, although this study does not claim a quantitative improvement in students' reading ability.